2006
DOI: 10.1373/clinchem.2005.065847
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Individual Microbial Pathogens by Proximity Ligation

Abstract: Background: Nucleic acid amplification allows the detection of single infectious agents. Protein-based assays, although they provide information on ongoing infections, have substantially less detection sensitivity. Methods: We used proximity ligation reactions to detect proteins on bacteria and virus particles via nucleic acid amplification. Antibodies recognizing viral or bacterial surface proteins were equipped with DNA strands that could be joined by ligation when several antibodies were bound in proximity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 19 publications
1
50
0
1
Order By: Relevance
“…This was shown by PLA, which is a modern technology to study protein-protein interactions. 32,33 PLA has been used in the past to detect parvovirus and an intracellular bacterium 34 and our data indicate that it may become an important tool to investigate and verify binding of native and modified viruses and other pathogen to cell surface molecules. The PLA assay also revealed that insertion of FWKT motif in the HI loop allowed for binding to SSTR 2 but did not completely abolish CAR binding.…”
Section: Oncolytic Adenovirus With Somatostatin Motifs J Leja Et Almentioning
confidence: 89%
“…This was shown by PLA, which is a modern technology to study protein-protein interactions. 32,33 PLA has been used in the past to detect parvovirus and an intracellular bacterium 34 and our data indicate that it may become an important tool to investigate and verify binding of native and modified viruses and other pathogen to cell surface molecules. The PLA assay also revealed that insertion of FWKT motif in the HI loop allowed for binding to SSTR 2 but did not completely abolish CAR binding.…”
Section: Oncolytic Adenovirus With Somatostatin Motifs J Leja Et Almentioning
confidence: 89%
“…The most robust method aptamer-mediated amplifications have been obtained using the proximity ligation assay (PLA), in which adjacent binding of two aptamers to a protein or cellular target results in ligation and formation of a unique amplicon which can then be sensitively detected by real-time PCR [12][13][14][15][16][17]. Fredriksson and co-workers originally showed that aptamer-mediated PLA could be used for the detection of zeptomole amounts of plateletderived growth factor (PDGF) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Proximity ligation assay is an ultrasensitive and specific method for detection of proteins and other analytes (9,17,23 ). We used 3 monoclonal antibodies; PSA-API was captured to the solid phase by a mAb against tPSA and detected by 2 mAbs labeled with DNA probes, 1 mAb against API and 1 mAb against tPSA.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences of the oligonucleotide probes, primers, and connector used in this assay have been described (17 ). We obtained the DNA connector and primers from TAG Copenhagen and TaqMan probe (5Ј FAM, 3Ј MGB) from Applied Biosystems UK.…”
Section: Oligonucleotides Used For Proximity Ligationmentioning
confidence: 99%
See 1 more Smart Citation